Determination of the mechanism of deoxygenation and hydropeneoxygenation of lauric acid using FeMo/AC catalyst for jet fuel production (penentuan mekanisme pendeoksigenan dan hidropendeoksigenan asid laurik menggunakan mangkin femo/ac untuk penghasilan biobahan api jet) - Mijan, Nurul Asikin; Yi, Megan Xin; Ravindran, Ravindran; Adzahar, Nur Athirah; Auji, Muhammad Hasif; Muaallamin, Ilya Natasha; Alsultan Ghassan, AbdulKareem; Lee, Hwei Voon; Ong, Hwai Chuan; Derawi, Darfizzi; Mastuli, Mohd Sufri; Marliza, Tengku Sharifah (Penerbit Universiti Kebangsaan Malaysia, 2025)
The higher demand for the use of bio-jet fuel (BJF) in the aviation industry is one alternative to reduce carbon dioxide (CO2) emissions into the environment. Malaysia is rich in palm oil resources and palm kernel oil (PKO) which contain about 48% lauric acid (C12), can be use as a feedstock for BJF production. There are two methods to convert lauric acid to BJF, namely the catalytic deoxygenation (DO) method and the catalytic hydrodeoxygenation (HDO) method. DO can convert lauric acid to BJF through the reactions without hydrogen (H2) involving decarboxylation/decarbonylation (deCOx) processes to remove oxygen, producing hydrocarbon chains and CO2 alongside byproducts such as carbon monoxide (CO) and water (H2O). Meanwhile, HDO converts lauric acid to BJF by removing oxygen in the form of H2O in the presence of H2. In this study, both DO and HDO methods were used to produce BJF using FeMo/AC catalyst. The synthesized catalyst was characterized using several characterization techniques such as XRD, FESEM-EDX, BET, TPD, and VSM. The effect of reaction temperature on the resulting products was studied to determine the reaction mechanisms for both methods. The liquid products obtained were characterized using GC-FID and GC-MS, while the gas products were characterized using GC-TCD. The results showed that the simulation mechanisms for both DO and HDO reactions for lauric acid using FeMo/AC catalyst is very effective where the reaction producing a variety of hydrocarbon species.